2011
DOI: 10.1016/j.ijdevneu.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to restraint or predator stresses attenuates field excitatory postsynaptic potentials in infant rats

Abstract: Exposure to stress is known to change synaptic plasticity and results in long-term depression; further, this stress precipitates seizures. In the study described here, the prenatal restraint and predator stress models were used to test the hypothesis that indirect prenatal stresses influence hippocampal synaptic potentiation and may affect seizures susceptibility in infant rats. Pregnant female Wistar rats were divided into 3 groups: control, restraint-stressed, and predator-stressed groups. Both stressed grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…PS potentiates seizure in different animal models. To confirm this point, it has been reported that prenatal restraint and predator stresses potentiate pilocarpine‐induced seizure in rats (Ahmadzadeh, Saboory, Roshan‐Milani, & Pilehvarian, ; Saboory et al, ; Sadaghiani & Saboory, ). On the other hand, opioid system is one of the endogenous modulatory mechanisms that affect seizure susceptibility (Saboory et al, ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…PS potentiates seizure in different animal models. To confirm this point, it has been reported that prenatal restraint and predator stresses potentiate pilocarpine‐induced seizure in rats (Ahmadzadeh, Saboory, Roshan‐Milani, & Pilehvarian, ; Saboory et al, ; Sadaghiani & Saboory, ). On the other hand, opioid system is one of the endogenous modulatory mechanisms that affect seizure susceptibility (Saboory et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…Many reports have shown that stress during gestation can induce early and long‐lasting effects on neurobehavioral development in rats. Previous works have demonstrated that prenatal restraint and predator stresses potentiate epileptic behaviors and increase susceptibility to seizures in offspring rats (Ahmadzadeh, Saboory, Roshan‐Milani, & Pilehvarian, ; Saboory, Ahmadzadeh, & Roshan‐Milani, ; Sadaghiani & Saboory, ). Morphine abuse during gestational period also produces long‐term alterations in CNS, alters density of hypothalamic opioid receptors and affects seizure susceptibility of the exposed animals (Vathy, ).…”
Section: Introductionmentioning
confidence: 99%
“…Predator stimuli are stressful for rats and mice. Exposure to natural predators and their odors elevate monoaminergic and stress hormone release in rats (Adamec et al, 1998; Saboory et al, 2011) and mice (Belzung et al, 2001). Therefore, to obtain more accurate results, both types of stress were applied in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The potentiation of seizures by PS has been reported and is presumably caused by an imbalance between the excitatory and inhibitory systems. There are neurobiological bases for stress‐induced seizures: exposure to stressors evokes hippocampal plasticity (Saboory et al, 2011), induces noradrenergic neurotransmission, and facilitates adrenocortical hormone activation (Edwards et al, 2002; Sadaghiani and Saboory, 2010). Our current findings demonstrated that PS potentiated pilocarpine‐induced seizures.…”
Section: Discussionmentioning
confidence: 99%
“…After parturition, the mother and her pups were moved to a new cage and number of pups culled to 8 at each litter. On the P14 and P21 (Hashemi et al, 2016; Saboory et al, 2011; Tavassoli et al, 2013), a male (n = 6 in each group) and a female (n = 6 in each group) from each litter were decapitated under ether anesthesia and entire hippocampus was removed quickly and placed inside the normal saline ice. Then, 50 mg tissues were homogenized in one ml RiboEX (Gene all, South Korea) solution, which is a protective solution of RNA.…”
Section: Methodsmentioning
confidence: 99%